Development of national identity in Armenia at the beginning of the 20th century based on primary capacities - Anahit Haykazuni (The Global Psychotherapist)
We improve ourselves each year based on our experience. That experience is passed on to us by our tribe. The generations that preceded us pass on to us a system of capacities that contribute to preserving existence. The lack or absence of information about those predecessors can lead to life-threatening consequences. Having lived through many crisis moments in its history, Armenia continues its existence, keeping its connection with its ancestors through the realization of national identity. National identity, the sense of belonging and attachment to one’s nation, is an important part of personality development. In the article, the author reveals the primary actual capacities involved in forming and reproducing national identity, as well as the connection between the transcultural approach and national identity.